ABBREVIATION FORMS IN JAVANESE LANGUAGE (BENTUK-BENTUK ABREVIASI DALAM BAHASA JAWA) - Madda Yadal Musaa'adah; Ardian Yuliani Saputri (UIN Raden Mas Said Surakarta, 2019)
This research was motivated by the use of abbreviations in communicating using Javanese. People prefer to use abreviations because they are shorter, faster, easier to remember, and easier to memorize. The purpose of this study is to classify the forms of abreviation, describe the patterns of the formation process, and describe the meanings of abreviations in the Javanese language, namely aferesis, syncope, and apocopy. Abreviation is a process of dating one or several parts of lexeme or a combination of lexemes that form a new form in the form of words. This study uses a qualitative-descriptive approach. The method of collecting data used proficient methods and referring methods. The data sources of this research were magazine articles in the form of written data of Javanese lexicons in the articles containing abreviations. In this study the abbreviations in the form of apheresis were found to be the highest number compared to abbreviations in the form of syncope and apocopy.